Pengelolaan Kawasan Pariwisata (Studi di Balai Besar Taman Nasional Bromo Tengger Semeru) - Utami, Hadi Sri (Jurnal Ilmiah Administrasi Publik, 2017)
A large number of tourists, both local and foreign, have an impact on coservation in this national park area. The rating of tourists hygiene awareness is considered low inducing pollution in the form of waste which is commonly found in the tourist area of Mount Bromo. This thesis aims to determine, identify and analyze the management of tourist area conducted by Balai Besar of Bromo Tengger Semeru National Park (Balai Besar TNBTS) of Mount Bromo from the perspective of public administration functions known with the acronym âPOSDCORBâ (Planning, Organizing, Staffing, Directing, Coordinating, Reporting, Budgeting which was proposed by Gullick. This study alsoÂ  has purpose to identify and analyze factors affecting the management of tourism area of Mount Bromo. This research uses qualitative method with descriptive approach. Research result shows that the management of tourism area of Mount Bromo conducted by Balai Besar TNBTS is not optimum due to some constraints in perspective of planning, staffing, and budgeting.